2012
DOI: 10.1007/s13337-012-0118-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Recombinant Citrus tristeza virus Isolate Occurring in Acid Lime cv. Pant Lemon Orchard in Uttarakhand Terai Region of Northern Himalaya in India

Abstract: The present study for the first time describes biological and molecular characterization of Citrus tristeza virus (CTV) occurring in the Terai area of Uttarakhand State in Northern Himalaya region of India. Direct antigen coated-ELISA and reverse transcriptase-polymerase chain reaction (RT-PCR) detected the CTV infection in Acid lime cv. Pant lemon (Citrus aurantifolia) orchards of Pantnagar with an estimated disease incidence of 16.6-20.5 %. To know the biological and genetic properties, an isolate, CTV Pant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Evidence for recombination events in the origin of many divergent CTV isolates has been documented earlier in India (Sharma et al, 2011, Biswas et al, 2012Singh et al, 2013). The present study determined that isolates 37 and K38 are recombinant isolates.…”
Section: Recombination In Ctv Isolatessupporting
confidence: 72%
See 1 more Smart Citation
“…Evidence for recombination events in the origin of many divergent CTV isolates has been documented earlier in India (Sharma et al, 2011, Biswas et al, 2012Singh et al, 2013). The present study determined that isolates 37 and K38 are recombinant isolates.…”
Section: Recombination In Ctv Isolatessupporting
confidence: 72%
“…CTV is present wherever the citrus is grown naturally or commercially in India (Ahlawat, 1997;Biswas, 2008;Biswas et al, 2014). CTV causes leaf yellowing, growth cessation, chlorosis, plant stunting with poor fruit yield and quality, and ultimately tree decline in India (Chakroborty et al, 1992;Biswas, 2008;Sharma et al, 2011;Singh et al, 2013;Biswas et al, 2014). Northeastern Himalayan region of India is known to produce mandarin, called Darjeeling mandarin (C. reticulata) commercially.…”
Section: Introductionmentioning
confidence: 99%
“…CTV shows diverse disease syndromes in different citrus species, indicating the occurrence of highly diversified CTV populations in India [7,8]. Extensive genetic diversity in CTV from different citrus-growing regions of India was reported [7,8,9,10,11,12]. At the international level, six distinct CTV genotypes (VT, T36, T30, T3, RB, and T68) and one recombinant entity (HA16-5) were recognized based on phylogenetic analysis of several complete CTV genomes [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Of them VT genotype has been described as biologically severe, T30 as mild and T36 as intermediate CTV strain [3]. It has also been suggested that homologous and nonhomologous recombination are major factors in the evolution CTV variants in India and other countries [5,18,20,23,30].…”
Section: Introductionmentioning
confidence: 99%